Implementation of Islamic Criminal Law (Syariah Offences) in a modern democratic federal country: the legal and constitutional issues and challenges in Malaysia - Mokhtar, Khairil Azmin (2015)
Upon its Independence the Federation Malaya 1957 which later become the Federation of Malaysia in 1963 the country inherited British legacy in most aspects of law, constitution, administration and political system. Before been colonized through direct and indirect means the Malay States or the Malay Muslim Sultanates had their own traditional polity and laws based on Islam. The teachings of Islam have been assimilated in the Malay culture, tradition and custom for centuries. The colonial authority, namely the British, gradually replaced Islamic law and judges as well as traditional rulers and local form of administration with western administration and administrators who then used English law and legal system. In effect, local Islamic law and administration of justice been replaced with foreign colonial law and justice system. After the Independence, citizenship was granted to the Chinese and Indian immigrants which constitute significant minority of the population of the newly independent country. This causes a great change of demography changing a homogenous society to multiracial and multi-religious society. Currently there are two sets of courts in Malaysia, the Civil Court and the Syariah Court. Numerous factors must be considered in the effort if enforcing Islamic criminal law in a country today, such as politic, social, legal, economy, human rights and others. There are various challenges need to be overcome in the effort of implementing Islamic criminal law in Malaysia. This paper seeks to focus its attention to the legal and constitutional issues and challenges in the effort to implement Islamic criminal law in Malaysia. The experience in Malaysia may provide some insight and basis of comparison for other countries in seeking similar objectives.